Transient facilitation of resprouting shrubs in fire-prone habitats - Paniw, M; Salguero-Gomez, R; Ojeda, F (Oxford University Press, 2017)
Aims Fires play a crucial role mediating species interactions in the Mediterranean Basin, with one prominent example being the nursing effect of post-fire resprouting shrubs on tree recruits, which then outcompete their benefactors throughout succession. Yet, the community structuring role of resprouting shrubs as potential facilitators of post-fire recruiting subshrub species, which are commonly outcompeted in late post-fire stages, has been overlooked. The aims of this work were to investigate (i) whether proximity to resprouting shrubs increased the demographic performance of a fire-adapted carnivorous subshrub and (ii) whether mature shrubs negatively affected the performance of established plants through interference with prey capture. Methods To evaluate the facilitative effects of resprouting shrubs, we sowed seeds of Drosophyllum lusitanicum, a carnivorous, seeder pyrophyte, into two microhabitats in recently burned heathland patches defined by proximity to resprouting shrubs. We monitored key demographic rates of emerged seedlings for 2 years. To test for competitive effects of shrubs on plant performance at a later habitat regeneration stage, we placed greenhouse-reared, potted plants into distinct microhabitats in neighboring burned and unburned heathland patches and monitored prey capture. Both experiments were performed in the Aljibe Mountains at the Northern Strait of Gibraltar and were replicated in 2 years. Important Findings Resprouting shrubs significantly improved survival, juvenile size and flowering probability compared with open microhabitats, and had no significantly negative effects on the growth of recruits. Prey capture was significantly lower in unburned heathland patches compared with burned ones, thus partly explaining the decrease in survival of Drosophyllum individuals in mature heathlands. However, microhabitat did not affect prey capture. Our findings suggest that not only periodic fires, removing biomass in mature stands, but also resprouting neighbors, increasing establishment success after fire, may be important for the viability of early successional pyrophytes.